Let us consider a first order reaction,

A → product

Suppose at the beginning of the reaction, that is, when t=0, the concentration of A is amolL and when t=t, the concentration of A is (a-x)molL.

For a first order reaction, the rate of reaction,

where k is the rate constant.

integrating,

Here, c is the constant of integration.

At, t=0, x=0 ; then from equation (i) we have,

putting the value of c in equation (i), we get,

ln a – ln(a-x) = kt

Equation (ii) is the required expression.

Unit of k:

From equation (ii) we found that the unit of k depends on the unit of t . The unit of k may be s-1, min-1, h-1, day-1 and so on.

A → product

Suppose at the beginning of the reaction, that is, when t=0, the concentration of A is amolL and when t=t, the concentration of A is (a-x)molL.

For a first order reaction, the rate of reaction,

where k is the rate constant.

integrating,

Here, c is the constant of integration.

At, t=0, x=0 ; then from equation (i) we have,

putting the value of c in equation (i), we get,

ln a – ln(a-x) = kt

Equation (ii) is the required expression.

## ContentMiddleAd

Unit of k:

From equation (ii) we found that the unit of k depends on the unit of t . The unit of k may be s-1, min-1, h-1, day-1 and so on.